Treatment with the Nitric Oxide Donor SNP Increases Triiodothyronine Levels in Hyper- and Hypothyroid Sprague-Dawley Rats - Ragginer, C.; Bernecker, C.; Ainoedhofer, H.; Pailer, S.; Kieslinger, P.; Truschnig-Wilders, M.; Gruber, H.-J. (Hormone and Metabolic Research, 2013)
Nitric oxide pathway might play a crucial role in the pathophysiology of thyroid dysfunctions. This study aimed to investigate the impact of nitric oxide (NO) on hypothyroid and hyperthyroid Sprague-Dawley rats under controlled diet. Furthermore, the effects of the nitric oxide donor sodium nitroprusside (SNP) on thyroid dysfunctions were also assessed. Sprague-Dawley rats (n=107) were subdivided into normal diet and high-fat diet (HFD) groups and grouped into controls, hypothyroid, hyperthyroid, and SNP treated groups. Hypothyroidism was induced through propylthiouracil, whereas hyperthyroidism by triiodothyronine (T3). After 12 weeks of T3 treatment, serum nitric oxides (NOX), endogenous asymmetric dimethylarginine (ADMA), body weight and food intake were analyzed. Hypothyroid rats showed decreased serum T3 levels, hyperthyroid rats increased T3 compared to controls. Diet had no impact on T3. Thyroid dysfunctions were accompanied by changes in calorie intake and body weight. Serum NOX was significantly reduced in normal diet hypothyroid rats. SNP administration compensated the decrease and markedly increased T3. NO synthase inhibitor ADMA levels were significantly higher in the HFD control group than in the normal diet controls. ADMA was declined in both hypothyroid groups and increased in normal diet hyperthyroid rats. An association of thyroid dysfunctions with reduced bioavailability of NO and alterations of ADMA levels could be established. Treatment with the NO donor SNP resulted in an increase of serum T3 levels. These results demonstrate that the NO pathway is implicated in thyroid dysfunctions, which may be of clinical relevance.
Keywords: hyperthyroidism; hypothyroidism; NO pathway; asymmetric dimethylarginine